Metaverse and Education: A Future Without Boundaries - AL-Muallem, Nibal (Journal of Posthumanism, 2024)
In the era of vast cognitive progress and accelerated scientific advancement, the necessity of digital transformation in education has become paramount. Engaging in digital technology is essential to keep pace with this advanced scientific progress. Consequently, many modern technologies have emerged, such as artificial intelligence, chatbots, blockchain, and other technologies used across various sectors and fields including education, health, industry, and economics. Education, being the vital arena benefiting from digital transformation in its various facets—teachers, learners, content, and learning environments—has aimed primarily in this study to shed light on the use of Metaverse technology in education. It clarifies the benefits and areas enabled by Metaverse for education, highlighting some foreign and Arab experiences that have implemented Metaverse in education. The study also elucidates the added value of outputs resulting from the use of Metaverse in education, transitioning education to diverse worlds through digital electronic platforms available via subscriptions. These platforms allow selection of branches and educational materials that align with students’ qualifications, intelligence levels, and their ability to interact with virtual, augmented, and real realities, as well as artificial intelligence strategies.The results indicate that Metaverse technology can bring about a qualitative leap in education and initiate a real revolution across its various domains. From creating excitement and engagement in lessons, fosters an active learning environment where all educational paths interact, spanning virtual, augmented, and real realities, culminating in an extended reality. Metaverse technology enables teachers and learners to innovate, think creatively, and solve problems, thus making education more effective and responsive to learners’ needs and fostering an enthusiastic desire for learning. It creates an engaging environment for learners and facilitates the creation of experiential and practice-based educational content. Moreover, it supports continuous high-quality development of educational content. Education is an industry, and investing in it is economically and socially essential, aligning with the priorities of sustainable development.